FAKTOR-FAKTOR YANG MEMENGARUHI EARNING MANAGEMENT DENGAN GROWTH SEBAGAI VARIABEL KONTROL - Adithian, Kevin Andrew; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2024)
This research is conducted to analyze whether the size of a company and the leverage have positive impacts on earning management. As a comparison, this research also scrutinizes whether good corporate governance can give negative impacts on earning management. The sampling provided for this research utilise a purposive sampling, microsoft Excel 2019 and Eviews 12 student version to process the data. The research conducted to 48 manufacturing companies for the period 2017 until 2020 depicts that the size of a company and the leverage don't produce a positive impact on earning management, and that good corporate governance doesn't result in a negative impact. instead, it gives a positive influence. growth as control variable produce a positive impact on earning management.